Understanding Auditors’ Sense of Responsibility for Detecting Fraud Within Organizations - DeZoort, F. Todd (Journal of business ethics, 2018)
The objective of this study is to evaluate auditors’ perceived responsibility for fraud detection. Auditors play a critical role in managing fraud risk within organizations. Although professional standards and guidance prescribe responsibility in the area, little is known about auditors’ sense of responsibility for fraud detection, the factors affecting perceived responsibility, and how responsibility affects auditor performance. We use the triangle model of responsibility as a theoretical basis for examining responsibility and the effects of accountability, fraud type, and auditor type on auditors’ perceived fraud detection responsibility. We also test how perceived responsibility affects auditor brainstorming performance given the importance of brainstorming in audits. A sample of 878 auditors (241 external auditors and 637 internal auditors) participated in an experiment with accountability pressure and fraud type manipulated randomly between subjects. As predicted, accountable auditors report higher detection responsibility than anonymous auditors. We also find a significant fraud type × auditor type interaction with external auditors perceiving the most detection responsibility for financial statement fraud, while internal auditors report similar detection responsibility for all fraud types. Analysis of the triangle model’s formative links reveals that professional obligation and personal control are significantly related to responsibility, while task clarity is not. Finally, the results indicate that perceived responsibility positively affects the number of detection procedures brainstormed and partially mediates the significant accountability–brainstorming relation.